Identification of High-performance Workplaces on the Basis of the Methods of the Russian Federal State Statistics Service - Dolzhenko, Ruslan Alekseevich; Lobova, Svetlana Vladislavlievna (Economy of Regions, 2019)
Russian economy is characterised by lower labour productivity compared to many developing countries. This circumstance caused the appearance of various orders in presidential “May decrees”, including the orders to create 25 million high-performance workplaces (HPW), and increase labour productivity by 1.5 times. Moreover, these decrees led to the creation and implementation of the national project “Labour productivity and support of employment”. Scientists actively discuss what should be considered as a criterion for the HPW: labour productivity or wages. The latter criterion is an indicator of the HPW that the Federal State Statistics Service (Rosstat) uses for counting their number. The article analyses the results of studies in academia and approaches to the assessment and identification of high-performance workplaces. This study is based on Rosstat’s open data on the number of HPW in Altai Krai, Siberian Federal District, and in the country. These data were processed, graphically presented and analysed in dynamics and by factors. Further, we showed the dynamics of the growth of the number of HPW, correlation between the changes in this number and changes in the labour productivity index, the subsistence level of the working age population, the size of the average monthly wage. Additionally, we analysed the structure of the HPW from the standpoint of types of economic activity. One ofthe main conclusions is the imperfection of Rosstat approaches to identifying HPW. We have shown that the use of obviously imperfect methods distorts the initial idea of their creation as a driver of economic development, thereby directing the regulator towards erroneous management of such processes. The findings substantiate the need for continuous updating and improving the competencies of highly educated personnel, and creating comfortable working conditions for employees (including sanitary, psychological, social, material ones).